Synthesis of silver nanoparticles and their role against human and Plasmodium falciparum leucine aminopeptidase - Mnkandhla, Dumisani (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2015)
Antimalarial drug discovery remains a challenging endeavour as malaria parasites continue to develop resistance to drugs, including those which are currently the last line of defence against the disease. Plasmodium falciparum is the most virulent of the malaria parasites and it delivers its deadliest impact during the erythrocytic stages of the parasite's life cycle; a stage characterised by elevated catabolism of haemoglobin and anabolism of parasite proteins. The present study investigates the use of nanotechnology in the form of metallic silver nanoparticles (AgNPs) against P. falciparum leucine aminopeptidase (PfLAP), a validated biomedical target involved in haemoglobin metabolism. AgNPs were also tested against the human homolog cytosolic Homo sapiens leucine aminopeptidase (HsLAP) to ascertain their selective abilities. PfLAP and HsLAP were successfully expressed in Escherichia coli BL21(DE3) cells. PfLAP showed optimal thermal stability at 25 Â°C and optimal pH stability at pH 8.0 with a Km of 42.7 mM towards leucine-p-nitroanilide (LpNA) and a Vmax of 59.9 Î¼mol.mlâ »Â¹.minâ »Â¹. HsLAP was optimally stable at 37 Â°C and at pH 7.0 with a Km of 16.7 mM and a Vmax of 17.2 Î¼mol.mlâ »Â¹.minâ »Â¹. Both enzymes exhibited optimal activity in the presence of 2 mM MnÂ²â º. On interaction with polyvinylpyrrolidone (PVP) stabilised AgNPs, both enzymes were inhibited to differing extents with PfLAP losing three fold of its catalytic efficiency relative to HsLAP. These results show the ability of AgNPs to selectively inhibit PfLAP whilst having much lesser effects on its human homolog. With the use of available targeting techniques, the present study shows the potential use of nanotechnology based approaches as "silver bullets" that can target PfLAP without adversely affecting the host. However further research needs to be conducted to better understand the mechanisms of AgNP action, drug targeting and the health and safety issues associated with nanotechnology use.
Keywords: Silver; Nanoparticles; Plasmodium falciparum; Leucine aminopeptidase; Antimalarials; Nanotechnology